Steal [compact disc, unabridged] - Patterson, James, 1947-; Roughan, Howard (Hachette Book Group, 2022)
Carter von Oehson posts on Instagram that he plans to kill himself. When no body turns up, Carter's father knows he's still alive. He only trusts Dr. Dylan Reinhart and Elizabeth Needham with the secret to how he knows this.